DIFFICULTIES AND OPPORTUNITIES FOR CREATIVE ECONOMIC DEVELOPMENT IN THE SOCIETY 5.0 ERA - Raharjo, Itot Bian; Lasmiatun, KMT; RiziqiFath, Zain Fuadi Muhammad; Mulyapradana, Aria; Kartamihardja, Sobarna (PT. Altin Riset Publishing, 2023)
This research aims to analyze the challenges and opportunities for creative economic development in the era of society 5.0. The research method used in this research is qualitative research. Qualitative research is a research method used to understand social phenomena in depth. This type of research is library research, which researchers carry out by collecting, studying, and analyzing references or sources. obtained in writing or written form, such as books, journals, articles, documents, and other sources of information that are significant to the topic or title being researched. The research results show that development economy creativity in Indonesia in the Society 5.0 era reflects a significant transformation in the methods used to create, produce, and promote products and services. Technology has become the primary driver of growth in the creative economy, as well as temporary creativity, local culture, and collaboration. Temporary, there is a challenge. Supporting the government and initiatives by private companies has helped push the development economy creatively in Indonesia. Taking lessons from the success period, then utilizing the opportunity period In the future, Indonesia can do it. Continue to develop as a key player in the global creative economy in the Society 5.0 era.